The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s11671-017-2169-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Delivery of Artesunate Enhances the Anti-tumor Efficiency by Activating Mitochondria-Mediated Cell Apoptosis

Abstract: Artemisinin and its derivatives were considered to exert a broad spectrum of anti-cancer activities, and they induced significant anti-cancer effects in tumor cells. Artemisinin and its derivatives could be absorbed quickly, and they were widely distributed, selectively killing tumor cells. Since low concentrations of artesunate primarily depended on oncosis to induce cell death in tumor cells, its anti-tumor effects were undesirable and limited. To obtain better anti-tumor effects, in this study, we took adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…Lysosomes contain high levels of redox-active iron and iron-catalyzed lysosomal ROS production leads to mitochondrial outer membrane permeabilization and apoptosis in response to specific stimuli [23] . It is consistent with many studies [24] , [25] , [26] that ART treatment leads to mitochondrial ROS accumulation, disruption of mitochondrial membrane potential and induction of the intrinsic mitochondrial apoptosis. However, it remains unknown whether these damaged mitochondria could be degraded through mitophagy.…”
Section: Introductionsupporting
confidence: 92%
“…Lysosomes contain high levels of redox-active iron and iron-catalyzed lysosomal ROS production leads to mitochondrial outer membrane permeabilization and apoptosis in response to specific stimuli [23] . It is consistent with many studies [24] , [25] , [26] that ART treatment leads to mitochondrial ROS accumulation, disruption of mitochondrial membrane potential and induction of the intrinsic mitochondrial apoptosis. However, it remains unknown whether these damaged mitochondria could be degraded through mitophagy.…”
Section: Introductionsupporting
confidence: 92%
“…A variety of nanotechnology has been developed in the past years to improve the solubility and bioavailability of ART. [23][24][25][26] ART loaded liposomes were reported with glioma targeting capabilities with enhanced toxicity towards glioma U87 cells. 27 Jin et al reported artesunate nanoliposomes, prepared with cholesterol and an appropriate amount of lecithin via thin film hydration method, showing stronger antitumor effect on HepG2 cells than that of free artesunate.…”
Section: Introductionmentioning
confidence: 99%
“…Albumin NPs were also applied for AS encapsulation. The comparison with free AS, the nanosystems presented cytotoxicity and significant apoptotic effects indicating activated mitochondrial-mediated cell apoptosis [31]. Herein, PNs indicate their potential to encapsulate ART and its derivatives and the use in cancer and protozoal diseases with high therapeutic efficacy (Table 1).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 92%